Prilika o izgubljenem sinu med besedo in sliko - Selan, Jurij (Primerjalna književnost, 2016)
In the article the author explores how the Bible could be art theoretically "read" in biblical paintings. Most hermeneutical approaches towards the problem are art historical in nature, focusing on standardised visual symbols in biblical artworks. However, less research is concerned with the formal nature of biblical artworks, that is with the understanding how in biblical paintings, the Bible could be "read" through shapes and their spatial and compositional relations. In the article the author exemplifies this hermeneutical problem by comparing The Parable of the Prodigal Son and Rembrandt's painting The Return of the Prodigal Son.
Keywords: Rembrandt: Vrnitev izgubljenega sina; književnost; literature; likovna umetnost; visual arts; svetopisemski motivi; biblično slikarstvo; likovne analize